HUBUNGAN KELENTUKAN PERGELANGAN TANGAN DAN KOORDINASI MATA-TANGAN DENGAN SHOOTING FREE THROW PADA TIM BASKET SAMBA PEKANBARU - Wirvansuseno Wirvansuseno; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on observations on the Pekanbaru Samba basketball team in the match, it has not found optimal shooting free throws, often the shots hit the board and ring without any point and also the observation that the author saw on the Pekanbaru Samba basketball team. average get a free throw penalty 3-4 times, and only able to put the ball into the ring 2 times. So as to make the team defeat in the match. This research was conducted on the Samba Pekanbaru basketball team with many samples of 12 people. The instruments in this study are wrist flexibility, eye and hand coordination and free throw shots. The results obtained are analyzed using product moment correlation. Based on the results of research and management of data using research statistical procedures, it was concluded that: From the results obtained there is a strong relationship between wrist flexibility and the results of the free throw of the Samba Pekanbaru basketball team namely the acquisition of r count (0.652)> from the acquisition of rtable (0.602) on α = 0.05. From the results obtained there is a strong relationship of eye-hand coordination with the results of the free throw of the Samba Pekanbaru basketball team, namely the acquisition of r count (0.718)> of the acquisition of rtable (0.602) at α = 0.05. There is a strong relationship between wrist flexibility and hand-eye coordination together with the results of the free throw of the Samba Pekanbaru basketball team, namely the acquisition of r count (0.760)> from the acquisition of rtable (0.602) at α = 0.05.Key Words: Wrist flexibility, eye-hand coordination, the results of the free throw